Comparison between Oral Delivery of Eudragit RSPO Microsphere-Based Matrix Tablet and Conventional Matrix Tablet: Comparison between Oral Delivery of Eudragit RSPO Microsphere-Based Matrix Tablet and Conventional Matrix Tablet - Singh, Kunwar Nagendra Krishna (International Journal of Pharmaceutical & Biological Archive, 2018)
The study aims at the comparative study of once-daily ziprasidone loaded polymeric microspheres-based (ZEmsp) matrix tablets (ZEmsp-T) as a sustained delivery system with conventional matrix tablets. The effect of variation in the drug/polymer ratio on the physicochemical characteristics of the microspheres was investigated. The optimized ZEmsp formulation demonstrated favorable mean particle size and drug loading along with sustained release pattern. After the selection of the optimized microspheres, matrix tablets were compressed with different direct tableting agents. After successful preparation and evaluation of ZEmsp-T, we found that batch ZEmsp-T3 and ZEmsp-T4, respectively. The optimized matrix tablets showed sustained release pattern of the drug release. The same parameters were evaluated for conventional matrix tablets, but results were not complies. Thus, results of this study prove the suitability of using Eudragit RSPO as a sustained release polymeric material to develop microspheres combined with different tableting agents to prepared matrix tablets were designed successfully for once-daily oral administration to avoid dosing frequency.